2017
DOI: 10.1007/s11528-017-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

MyWallMate: An Investigation into the use of Mobile Technology in Enhancing Student Engagement

Abstract: This paper is a report of an investigation in which mobile technologies were used during large lecture-type sessions in tandem with the Textwall™ software. This online program is able to receive and present messages from students' devices that the lecturer may then share. It also can be used to collect student votes on multiple-choice questions, facilitating dynamic formative assessments during class. A study has been undertaken around the MyWallMate mobile application. This program has been developed by Liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Students have noted that one of the factors that remained most appealing about using Poll Everywhere and other ARS's was the ability to use mobile devices as a part of their learning (Sellar, 2010;Shon & Smith, 2011;Warnich & Gordon, 2015). Research has found that students consider the smartphone to be useful not only to their daily lives but also to education and self-learning, an important factor in student engagement (Dobbins & Denton, 2017;Heflin et al, 2017;Khaddage, Muller, & Flintoff, 2016;Kukulska-Hulme & Shield, 2008). One study found that utilizing smartphones in lectures with an ARS increased student engagement among 86% of the students involved (Dobbins & Denton, 2017).…”
Section: Overview Of Poll Everywhere As An Arsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students have noted that one of the factors that remained most appealing about using Poll Everywhere and other ARS's was the ability to use mobile devices as a part of their learning (Sellar, 2010;Shon & Smith, 2011;Warnich & Gordon, 2015). Research has found that students consider the smartphone to be useful not only to their daily lives but also to education and self-learning, an important factor in student engagement (Dobbins & Denton, 2017;Heflin et al, 2017;Khaddage, Muller, & Flintoff, 2016;Kukulska-Hulme & Shield, 2008). One study found that utilizing smartphones in lectures with an ARS increased student engagement among 86% of the students involved (Dobbins & Denton, 2017).…”
Section: Overview Of Poll Everywhere As An Arsmentioning
confidence: 99%
“…Research has found that students consider the smartphone to be useful not only to their daily lives but also to education and self-learning, an important factor in student engagement (Dobbins & Denton, 2017;Heflin et al, 2017;Khaddage, Muller, & Flintoff, 2016;Kukulska-Hulme & Shield, 2008). One study found that utilizing smartphones in lectures with an ARS increased student engagement among 86% of the students involved (Dobbins & Denton, 2017).…”
Section: Overview Of Poll Everywhere As An Arsmentioning
confidence: 99%
“…Wireless technology, including laptops, tablet computers, and mobile phones is becoming increasingly popular. A number of studies indicate that the use of mobile devices in a classroom environment promotes students' motivation (emotional), participation (behavioral) and assists in collaborative learning (cognitive) (Barak, Lipson & Lerman, 2006;Dobbins & Denton, 2017;Kukulska-Hulme, 2013). Even though somewhat older technologies, in particular laptop computers have established their predominance in classrooms, mobile tools such as iPads and other tablet computers do offer other advantages such as better mobility, lightweight, convenience to carry, handwriting recognition, responsive touchscreen and ease of use, but are not found to be core academic tools for the majority of students (Crichton, Pegler & White, 2012;Dearnley, Haigh, & Fairhall, 2008;Hashim, 2014;Henderson, Selwyn, Finger & Aston, 2015;Morris et al, 2012;Murphy & Williams, 2011;Saorin et al, 2013;Sullivan, 2013;Tanaka et al, 2012;Author & Mang, 2015;Welsh et al, 2015).…”
Section: Popularity Of Mobile Devices In Classroomsmentioning
confidence: 99%
“…The logistical aspects relate to the more pragmatic tasks a university student has to perform on a daily basis, such as doing and submitting assignments, scheduling activities, retrieving documents, and a slew of other actions to remain socially and academically informed. These authors and others (Bennett and Maton, 2010;Dobbins & Denton, 2017;Margaryan et al, 2011) found that the dominant digital technology models of student learning were still more in tune with the typically conservative and passive consumption and transmission of knowledge than the mythically spectacular advancements postsecondary education institutions are loosely suggesting. Kinash et al (2012) and Rossing, Miller, Cecil, and Stamper (2012) presented results concerning students' perceptions of tablets based on the use of Apple iPads during one or more class sessions of a course.…”
Section: Learner's Acceptance Of Technology and Purpose Of Usementioning
confidence: 99%
See 1 more Smart Citation